Properties of the Adjoint Operator of a General Fuzzy Bounded Operator - Manar Naji Gheeab; Jehad R. Kider (مجلة بغداد للعلوم)
Our goal in the present paper is to recall the concept of general fuzzy normed space and its basic properties in order to define the adjoint operator of a general fuzzy bounded operator from a general fuzzy normed space V into another general fuzzy normed space U. After that basic properties of the adjoint operator were proved then the definition of fuzzy reflexive general fuzzy normed space was introduced in order to prove that every finite dimensional general fuzzy normed space is fuzzy reflexive.